PENGETAHUAN SWAMEDIKASI DISMENOREA SISWI SMK SEMESTA BUMIAYU TAHUN 2020 - Dian Trimajaya; Luthfi Hidayat Maulana; Tunjung Winarno (Jurnal Farmasi Universitas Peradaban, 2021)
This research is entitled "Knowledge of Dysmenorrhea Self-Medication for Female Students of “SMK Semesta Bumiayu” Academic Year 2020. Dysmenorrhea is a problem that often occurs to the women during menstruation period. This study aims to determine the knowledge of dysmenorrhea and dysmenorrhoea self-medication to the Female students of “SMK Semesta Bumiayu”. This research is a descriptive quantitative study using a total sampling technique of 252 female students as the respondents. The collected data were analyzed using descriptive analysis technique with the help of the SPSS for windows version 16 application. The results of data analysis showed that most respondents had a good knowledge level of dysmenorrhea (54.8%), and knowledge of dysmenorrhea self-medication with a moderate category (57.1%.).